Eksperimen Strategi Pembelajaran Discovery Learning dan Project Based Learning terhadap Hasil Belajar Matematika Ditinjau dari Gaya Belajar Siswa Kelas X SMK Muhammadiyah Delanggu Tahun Ajaran 2014/2015 - Citrannissa, Chanivah Fitra, Prof. Dr. Sutama, M.Pd, M. Noor Kholid, S.Pd., M.Pd (2015)
There are three aims of the research. (1) Examine the contribution of Discovery Learning and Project Based Learning strategy toward mathematics learning achievement. (2) Examine the contribution of learning style toward mathematics learning achievement. (3) Examine the interaction between learning strategy and learning style toward mathematics learning achievement. The type of the reaserch was a quantitative research with quasi experimental design. The population was 230 in nine class of X grade students of SMK Muhammaduyah of Delanggu. The sample of the research was 2 class that determined by random sampling. The data were collected by test, documentation, and quisioner methods. The data were analyzed by using the unbalanced two-way analysis of variance. The findings of the research with